Personalized cosmetic products. News and perspectives. - Roncea, Florentina-Nicoleta; Cazacincu, Radu-George; Mireșan, Horațiu; Roșca, Adrian-Cosmin; Erimia, Cristina-Luiza (Technium BioChemMed, 2023)
In a competitive and stressful world that demands vitality, energy and good health, cosmetics play an increasingly important role for individuals and society as a whole. In this context, customization is a prominent strategy in the beauty industry that can satisfy varied customer preferences. Today’s personalized cosmetics can be defined as three major types: (a) previously made by manufacturers according to customer needs (made-to-order services), (b) do-it-yourself (DIY) kits provided for the manufacture of cosmetics by customers themselves at home or (c) performed on site (in situ) by sellers or customers. Most personalized cosmetics belong to type a or b, where safety and quality are previously ensured by the manufacturers. These are considered general commercial cosmetics; therefore, the final products should comply with regulations such as the Cosmetic Act of the Republic of Korea, and EC Cosmetic Regulation 1123/2009 in Europe (European Commission, 2009). Meeting legal regulations for customized cosmetic products can be a challenge, but compliance is achievable in most situations, especially by the Korean Country market through the Cosmetic Act update. The South Korean Ministry of Drug and Safety (MFDS), in March 2020, introduced the world’s first regulatory guidelines on custom (personalized) cosmetics. Also, in april 2023, Shanghai issued its first license for on-the-spot on site (in situ) personalized cosmetics service, marking the launch of a pilot program for such a service in the city. In the European Union, from this perspective, a customized cosmetic product on the market (online purchase with production at regular facilities; mixing in situ; mixing with a household device; mixing boosters with a cosmetic base), does not ensure total compliance with the regulations in the field. A new, updated guide harmonizing the regulations for personalized cosmetic products should enable best practices for the single market, ensuring their quality and safety.